Fitting non-gaussian Models to Financial data: An Empirical Study - Olivares, Pablo (2004)
In this paper are presented some experiences about the modeling of financial data by three classes of models as alternative to Gaussian Linear models. Dynamic Volatility, Stable Lévy and Diffusion with Jumps models are considered. The techniques are illustrated with some examples of financial series on currency, futures and indexes.